GENELLEŞTİRİLMİŞ İSTATİSTİKSEL YAKINSAKLIK - YÜZBAŞI, BAHADIR (Fırat Üniveristesi, 2010)
Bu çalışma dört bölümden oluşmaktadır.Birinci bölümde; bazı temel tanım ve teoremler verilmiştir.İkinci bölümde; istatistiksel yakınsaklık ve kuvvetli p-Cesàro toplanabilme kavramları incelenmiştirÜçüncü bölümde; . dereceden istatistiksel yakınsaklık ile . dereceden kuvvetli p-Cesàro toplanabilme kavramları verilmiş, bu kavramlar karşılaştırılmıştır.Dördüncü bölümde; . dereceden istatistiksel değme noktaları ve sınırlılık ile . dereceden istatistiksel üst ve alt limit kavramları verilmiş olup, bu bölüm tezin orijinal kısmını oluşturmaktadır.

This study is prepared as four chapter.In the first chapter; some fundamental definitions and theorems are given.In the second chapter; the concepts of statistically convergence and strong p-Cesàro convergence are examined.In the third chapter; the ideas of statistical convergence and strong p-Cesàro convergence of order are given and then this concepts are compared.In the fourth chapter; the notions of statistical cluster points and boundedness of order and the concepts of statistical limit superior and limit inferior of order are given. This chapter is an original part of the thesis.
Generalized statistical convergence
Keywords: Matematik